FRI0629 Magnetic resonance imaging (MRI) inflammation of the feet demonstrates subclinical inflammatory disease in cutaneous psoriasis patients without clinical arthritis. (15th June 2017) - Mathew, AJ; Bird, P; Gupta, A; George, RE; Danda, D
Abstract : Background: Up to 40% of patients with cutaneous psoriasis may develop psoriatic arthritis (PsA). Early detection of PsA by advanced imaging techniques results in better response to therapy. There are very few studies evaluating the MRI appearance in feet of patients with psoriasis and PsA. Objectives: This study sought to evaluate inflammation at the small joints of feet in a subset of psoriasis patients without clinical arthritis, using an office-based extremity MRI (eMRI) as compared to the findings in overt PsA patients. Methods: Patients with psoriasis were recruited from Dermatology and Rheumatology clinics of a tertiary care institution in southern India were divided into those without arthritis (PsO) and PsA groups. All consenting patients underwent non-contrast eMRI of the right foot. Demographic and physical examination details were recorded. PsO patients completed the early arthritis in psoriasis (EARP) questionnaire. Two trained readers scored the MRI inflammation (synovitis, tenosynovitis, osteitis) using a modification of the PsAMRI scores (PsAMRIS). 1 Inter-reader agreement was assessed in a random subset of 42 cases using intra-class correlation coefficient (ICC). Proportion of patients with any sign of MRI inflammation was noted. Mann-Whitney U test was used to compare inflammation scores of PsO with PsA patients. Clinical variables were compared with inflammation scores for any association. Results: A total of 83 patients (30 PsA and 53 PsO) with 75% males and mean age of 42.2±11.6 years were included. ICC for all three variables between the readers was very good (>0.8). There was no statistical difference between the median eMRI inflammatory scores in PsA and PsO patients (p=0.493). Evidence of inflammation was present in 64% and 67% patients in the PsO and PsA groups, respectively (Table 1 ). Higher NAPSI scores were associated with presence of MRI inflammation (p=0.022). Conclusions: This study corroborates a high proportion of psoriasis patients with subclinical disease of the small joints of foot. Patients with nail involvement had a higher risk of subclinical disease. The cohort is being assessed longitudinally to determine the clinical utility of MRI feet in predicting subsequent development of PsA in patients with psoriasis. References: Glinatsi D, Bird P, et al. Validation of the OMERACT psoriatic arthritis magnetic resonance imaging score (PSAMRIS) for the hand and foot in a randomized placebo-controlled trial. J Rheumatol 2015;42:2473–9. Acknowledgements: This project is being funded by the APLAR and Christian Medical College, Vellore research board. Disclosure of Interest: None declared